Challenges and Opportunities in Human Resource Management in Indonesian Law Enforcement: A Literature Review - Fitrianto, Arief; Suhariadi, Fendy; Nur Basuki Minarno (Technium Social Sciences Journal, 2025)
Law enforcement in Indonesia faces complex challenges, such as a lack of human resource competency, weak inter-agency coordination, and the impact of decentralization that hampers the effectiveness of institutions such as the police and the Corruption Eradication Commission. This study uses a literature review approach based on the Strategic Human Resource Management (SHRM) theory to explore the challenges and opportunities in human resource management in law enforcement. The research data were collected from literature originating from the Scopus database, focusing on geographically relevant articles (Indonesia) and published from 2000 to the present. The results of the study indicate that performance-based reforms, investment in training, utilization of digital technology, and strengthening inter-agency coordination can improve the effectiveness of human resource management. A humanistic approach to HRM can also strengthen personnel motivation and efficiency. Theoretically, this study enriches the literature on human resource management in developing countries. In contrast, managerially, this study offers practical recommendations for improving the recruitment, training, and performance evaluation systems in Indonesian law enforcement institutions.